2021
DOI: 10.1155/2021/2711365
|View full text |Cite
|
Sign up to set email alerts
|

Altered Regional Homogeneity and Functional Connectivity during Microlesion Period after Deep Brain Stimulation in Parkinson’s Disease

Abstract: Background. Patients with Parkinson’s disease (PD) undergoing deep brain electrode implantation experience a temporary improvement in motor symptoms before the electrical stimulation begins. We usually call this the microlesion effect (MLE), but the mechanism behind it is not clear. Purpose. This study aimed to assess the alterations in brain functions at the regional and whole-brain levels, using regional homogeneity (ReHo) and functional connectivity (FC), during the postoperative microlesion period after de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…30,[39][40][41] Wu et al 41 observed that PD patients had decreased regional homogeneity (ReHo) in the SMA compared to healthy controls. In a recent study, the ReHo of SMA was elevated during MLE after DBS surgery, 16 suggesting that DBS relatively normalized SMA activity. The prefrontal cortex helps plan, regulate, and control psychological activities.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…30,[39][40][41] Wu et al 41 observed that PD patients had decreased regional homogeneity (ReHo) in the SMA compared to healthy controls. In a recent study, the ReHo of SMA was elevated during MLE after DBS surgery, 16 suggesting that DBS relatively normalized SMA activity. The prefrontal cortex helps plan, regulate, and control psychological activities.…”
Section: Discussionmentioning
confidence: 94%
“…However, the sample size limited the result accuracy of the results 8 . Our previous work has demonstrated alterations in brain activation in motor‐related brain areas, such as the precentral gyrus and supplementary motor area (SMA), during microlesion after DBS 15,16 . However, they are yet to explore the change in the motor network.…”
Section: Introductionmentioning
confidence: 99%
“…Regional homogeneity (Reho) is a data-driven local measure of spontaneous neural activity that does not require the onset time of stimulation or prior knowledge and has good test–retest reliability ( Xia et al, 2018 ). Functional connectivity (FC) is an fMRI data processing method used to explore the functional interactions between anatomically separated brain regions ( Luo et al, 2021 ). Reho and FC are considered to be complementary in examining the synchronization of local and remote brain activity ( Sun et al, 2018 ),and the simple computations and reliable representations involved have led to their use in exploring brain diseases with underlying functional alterations, such as epilepsy ( Liu et al, 2021 ), Alzheimer’s ( Ibrahim et al, 2021 ), and depression ( Chen et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%